Honouring the Voices of the Ancestors - A Personal View of the Effect of Māori Language Immersion Education in Aotearoa-New Zealand - Mahuta, Dean (Te Kaharoa, 2011)
Many studies have been undertaken which focus on identifying factors which impact on the participation and achievement of Māori students in post compulsory education and factors contributing to Māori success in tertiary education. (Jefferies, R. 1997; Tiakiwai, S.J. 2001; Nikora, L. W., Levy, M., Henry, J., & Whangapirita, L. 2002; Greenwood, J., & Te Aika, L. 2009), One of the factors identified as an institutional barrier is a lack of recognition of Māori culture and language. This article discusses the importance of university Māori language students being able to write their assignments, dissertations and theses not only in the Māori language, but in their own tribal dialects. Using a case-study approach of the authors’ personal experiences of primary, secondary and tertiary education, the case-study will focus specifically on the place of the authors’ tribal identity and dialect in this process. Dialect will be illustrated through samples of work submitted for the authors BA (Hons) dissertation, MA and PhD. This will also demonstrate the importance of writing in the community language, when conducting research on a topic related to that community, and this will be discussed in terms of reflecting a commitment to the survival of that community language and to increasing the corpus of work being produced in the Māori language. This case-study, adopting a narrative approach, will demonstrate a positive outcome for both a university and a Māori student when a) the university provides the right pathways, policies and processes to empower Māori students to write in their native tongue; and b) the student has the courage and tenacity to continue writing in the Māori language and in their dialect, as a minority in the institution.